Exhaustion of digital goods: An economic perspective - Wolfgang Kerber (Philipps-University Marburg, School of Business and Economics, 2016)
The "UsedSoft" decision of the Court of Justice of the European Union (CJEU) about the right of a buyer of a downloaded copy of a software to resell this copy triggered a controversial discussion about the applicability of the "exhaustion" rule (US: first-sale doctrine) to copyright-protected digital goods (as, e.g., also e-books). This paper offers, in a first step, a systematic analysis and assessment of economic reasonings that have been discussed in the literature about exhaustion, and applies this framework, in a second step, to downloaded digital creative works. An important result is that digitalisation, on one hand, changes considerably the benefits and costs of exhaustion, esp. in regard to the danger of jeopardizing the incentives for copyright owners. On the other hand, however, also the costs of imposing restrictions might be high and even increase in a digital economy. This leads to the conclusion that it is necessary to think seriously about the legal limits for the restrictions that copyright owners should be allowed to impose on their customers. However, these limits might be drawn also by other legal instruments than copyright exhaustion.
Keywords: K20; L86; O34; 330; digital goods; copyright exhaustion; first-sale doctrine; post-sale restrictions